INTRODUKSI PROGRAM STUDI DAN PROSPEK KARIER LULUSAN ILMU ADMINISTRASI NEGARA PADA SISWA SMAN 1 SINABANG - Agus Pratama; Al Zuhri; Agatha Debby Reiza Marsella; Nurasma Aripin; Giovanni Oktavinanda; Siti Jahria Sitompul (Bakti Banua : Jurnal Pengabdian Kepada Masyarakat, 2023)
One of the problems in continuing tertiary education experienced by students is doubt and indecision in determining majors. Choosing the right major will determine the direction of your future career. So, to answer this problem it is necessary to carry out community service activities by introducing study programs and graduate career prospects. The purpose of implementing community service activities is to introduce the Public Administration study program and the profile achievements of graduates so that they become a reference for students in determining career directions according to their interests and aspirations. This service activity is carried out using the lecture method. The author conducted a pre-test and post-Test as a step to find out the extent of students' understanding of the Public Administration study program. As for the results of the community service activities during the pre-test, few participants knew about the existence of the Public Administration study program, but after the post-test was carried out, the students understood and knew about the studies and achievements of graduates of the Public Administration study program so that later it would become one of the list of major choices for students to build a future career.